Elements of Communication Competence in Encountering Traumatized Adolescents in Substitute Care - Leinonen Leena; Kaittila Anniina; Alin Minna; Vornanen Riitta; Karukivi Max; Kraav Siiri-Liisi; Anis Merja (Sage Journals, 2025)
Adolescents who need both child welfare services and mental health interventions have usually experienced various traumatic events in their early lifespan. The purpose of this study is to identify the elements of communication that can either empower traumatized adolescents in their rehabilitation process or become an obstacle in their recovery. The data consist of interviews of 19 young adults with a substitute care background. Their experiences of communication with welfare professionals in child welfare and mental health services during adolescence are analysed using the method of content analysis in a framework of communication competence that is outlined with four elements: cognitive, affective, behavioural and ethical. The role of communication is crucial while helping the adolescents. The trauma-informed capabilities of welfare professionals should be strengthened. Future research is needed on the processes, enabling the voice of this vulnerable clientele to be heard, here and in previous stages of services.